Case Report: An Unusual Case of Sudden Cardiovascular Collapse in an Elderly Adult - Bair, Aaron E; Ballard, Dustin; Thornton, Michael; Yoneda, Ken Y (Western Journal of Emergency Medicine, 2005)
In our report we describe a case of foreign body aspiration leading to arrest. The patient’s resuscitation was remarkable for the development of a large pneumothorax and atelectasis of the right lung. Aspiration was suspected and early bronchoscopy was performed. A large grape was found to be obstructing the right main stem bronchus and was retrieved using a bronchoscopic snare. In this case early intervention allowed the removal of the intact grape with subsequent re-expansion of the lung. The technique used for retrieval is described.